The system of entities providing territorial defence of Ukraine and the role of local self-government bodies within it - I. V. Romanskyi (Bulletin of Kharkiv National University of Internal Affairs)
It has been found that the system of entities providing territorial defence of Ukraine consists of: 1) The Verkhovna Rada of Ukraine is responsible for establishing the legislative framework for the territorial defence of Ukraine and for exercising parliamentary control over the compliance with the requirements of the legislation in this area by the committees established by it; 2) The President of Ukraine and the National Security and Defence Council of Ukraine are responsible for the global management and control over the functioning of the entire defence and security sector of Ukraine, including territorial defence, and ensure the deployment of territorial defence if necessary; 3) The Cabinet of Ministers of Ukraine, ministries and other central executive authorities whose activities are aimed at building the organisational and administrative architecture of territorial defence, determining the vector of development and implementation of the state policy in the field of defence and territorial defence of Ukraine; 4) target subjects of territorial defence implementation including regional state administrations, military authorities and law enforcement agencies. They are responsible for the proper implementation of territorial defence measures, the realisation of its functions, tasks and objectives, as well as the ongoing maintenance of their effectiveness; 5) local self-government bodies.